Transforming Islamic Education and Language Reinforcement: Empowering Learning with the Assure Model - Tsania fitramaulidia; Muhammad Adip Fanani (MultiTech Publisher, 2023)
This research explores the transformation of Islamic education with a focus on language strengthening through the application of the ASSURE learning model. Through a comprehensive literature review, this article uses sources such as books, journals, documents, and articles. The research results highlight the potential of the ASSURE model in improving students' learning experiences and expanding their understanding of religious teachings, thereby having a positive impact on the effectiveness of learning in the context of Islamic Religious Education. Continuous evaluation and adjustment were identified as key to ensuring sustainability and improved learning outcomes.